Exploration of the variations of amino acids in Massa Medicata Fermentata and their effects on gastrointestinal diseases. (1st January 2023) - Gao, Shengmei; Shan, Luyu; Shi, Yaling; Zhao, Yuting; Mu, Qixuan; Cui, Ying; Chai, Xin; Wang, Yuefei
Abstract: As a representative fermented Chinese medicine, Massa Medicata Fermentata (MMF) has been widely used for treating gastrointestinal diseases. Active amino acids are responsible for disease treatment. However, the transformation pattern from proteins as the primary ingredients to amino acids has not been fully unveiled during fermentation. Also, the variation rule has not been clarified during processing. In this study, as the potential capacity in treating gastrointestinal diseases predicated by network pharmacology analysis, amino acids were derived by phenyl isothiocyanate and analyzed in MMF. Notably, 14 amino acids converted from proteins in substrate were produced with the variation rates ranging from 3 to 89 during fermentation. The process of drying and stir-frying with bran exhibited limited influence ( P  > 0.05) except for Gly, Val, Ile, Leu, Phe, and Tyr ( P  < 0.05), while charring sharply decreased the contents of amino acids ( P  < 0.001). A great disparity of the quantified amino acids was witnessed among the commercially available samples, resulting from difference of materials composition and processing procedures. In general, these findings may contribute to an understanding of classic fermentation for MMF, which conduce to better clinical practice. Graphical abstract: Image 1 Highlights: Transformation pattern from proteins to amino acids in MMF was first elucidated. The UPLC-PDA method for the detection of amino acids in MMF was established. Effect of processing procedure on degrading behavior of amino acids was revealed. The role of amino acids in treating gastrointestinal disease was predicted.